An assessment of firm efficiency and the link to executive pay: A study of UK building societies - Mir, Ahmed (2012)
This study utilises an unbalanced panel data set of 41 U.K building societies from 1998 to 2011, examining the relationship between cost efficiency and CEO salary. Using maximum-likelihood I estimate the parameters of a stochastic cost frontier under a transcendental logarithmic functional form. The stochastic frontier analysis finds that on average building societies in the sample operate with a mean cost inefficiency of 18%. The latter stages of the investigation involve a regression analysis, which estimates the correlation between the cost efficiency of a smaller sample of building societies and CEO salary. Ultimately, the evidence presented in this paper finds that efficiency does not have a statistically significant impact on CEO remuneration but firm size has a substantial influence on executive pay levels.